‘It was like being hit with a brick’: a qualitative study on the effect of clinicians’ delivery of a diagnosis of eye disease for patients in primary and secondary care - Lucy Moore; Jasleen Kaur Jolly; Anne Ferrey (BMJ Open)
Objectives To explore patients’ experiences of getting a diagnosis of eye disease, the psychological impact of this and how this could be improved.Design An exploratory qualitative interview study using a narrative approach and inductive methods.Setting This study was conducted with patients who had attended ophthalmic appointments in primary and secondary care and in opticians located in the South of England.Participants 18 people diagnosed with eye disease in England.Results Four themes were identified: the convoluted process of being diagnosed, the impact of clinicians’ words, the search for information and reflections on what could be improved. The prolonged wait for a definitive diagnosis was a source of frustration and anxiety for many patients. Professionals’ words and tone when delivering a diagnosis sometimes affected a patient’s view of their diagnosis and their later ability to come to terms with it. Patients were desperate for information, but many felt they were not provided with sufficient information at the time of diagnosis and did not know whether to trust information found online. Participants felt the provision of a hospital liaison service and/or counselling could mitigate the impact on patients and families.Conclusions Interactions with clinicians can have a lasting impact on how a diagnosis is experienced and how well the patient is able to come to terms with their visual impairment. Receiving little or no information left patients feeling lost and unsupported. This led them to search for information from less reliable sources. Clinicians should consider how they communicate a diagnosis to patients, how and when they offer information about diagnosis and prognosis and where possible signpost patients to additional support systems and counselling services as early as possible.